Skrining fitokimia pada tanaman penyembuh luka di Lombok Timur - Fidrus Affandy; Dyke Gita Wirasisya; Nisa Isneni Hanifa (Universitas Mataram, 2021)
The ethnomedicinal study which conducted in East Lombok revealed 5 potentially plants that have wound healing properties (Jatropha multifida L., Stachytarpheta jamaicensis (L.) Vahl, Centella asiatica (L.) Urban, Euphorbia pulcherrima Willd, and Angelica keiskei). The five plants have been no further research related to the presence of compounds that have activity in wound healing. This study aims to screen the plants secondary metabolites from above plants. The sample was maserated with 96% solvent methanol. The viscous extract was determined by physical characterization including consistency and color as well as chemical characterization, namely the phytochemical screening test. The results showed that the five plants contained flavonoids, phenolics, saponins, and steroids, except for Stachytarpheta jamaicensis (L.) Vahl showed negative results for saponins and Angelica keiskei showed negative results for steroid compounds. Keywords: phytochemical screening, total phenolic content, wound healing herbs, East Lombok